Impact of Budget Participation on Managerial Performance with Locus of Control and Cost Management Knowledge as Moderating Variables - Bambang Jatmiko; Kurnia Diah Kinanti; Titi Laras (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to test and empirically prove the effect of budget participation on managerial performance with the locus of control and cost management knowledge as moderating variables in manufacturing companies in Tangerang City. The sample used was 38 managers involved in budgeting participation, consisting of middle- and lower-level managers. The type of data used is primary data. The method in this study uses purpose sampling. The data analysis tool in this study uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) through the SmartPLS v3.0 software application. The results of this study show that budget participation positively affects managerial performance, and cost management knowledge moderates the relationship between budget participation and organizational performance. At the same time, the locus of control cannot moderate budget participation towards managerial performance.